Potensi Pengembangan Pariwisata Local Wisdom Pada Lembang Baruppu’ Benteng Batu - Desrianti Ruru; Rati Kussu; Althon K Pongtuluran; Marinus Ronal (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
The potential for developing local wisdom tourism is part of human creativity. A tourist village is a tourist destination that reflects local tourism wisdom. Local wisdom tourism that exists in society is: customs, history, culture and natural beauty. Lembang Baruppu' Benteng Batu is located in Baruppu' sub-district, North Toraja district. It is a tourist village that has tourism potential in the form of natural tourism, customs, culture and history. The aim of this research is to analyze tourism potentials related to local wisdom tourism and recommend the potential for developing local wisdom tourism in Baruppu' Benteng Batu. The method used in the research is qualitative analysis through direct observation and interviews with local government, traditional leaders and the community. Some of the potential for developing local wisdom tourism in Baruppu' Benteng Batu are still being preserved today and some have been neglected.